Neurosurgical education during COVID-19: challenges and lessons learned in Egypt - Ashry, Ahmed Hamdy (Egypt J Neurol Psychiatr Neurosurg, 2020)
BACKGROUND: The coronavirus pandemic (COVID-19) has disrupted the routine neurosurgical education and practice worldwide and so more in developing countries. Continuing the neurosurgical training while maintaining the well-being of our residents should be the primary concern of leaders of training programs. OBJECTIVES: The aim of this cross-sectional study was the evaluation of the impact of COVID-19 on neurosurgical residency programs and neurosurgical practice in five tertiary medical centers in our country. We also aimed at detecting the shortcomings in training programs and provide solutions. METHODS: An online questionnaire-based survey was prepared and sent to 73 neurosurgery residents in 5 tertiary centers in 4 governorates by social networks. The questions focused on the evaluation of clinical and surgical activities before and after the pandemic. Safety precautions, education, and residents’ mental health were also evaluated. RESULTS: Fifty residents responded to our survey. We identified a significant reduction in surgical cases, inpatient services, and working hours per week during the pandemic comparing to the pre-pandemic era. We also identified a significant increase in research hours and changes in educational methods from in-person methods to virtual ones. Seventy-four percent reported that personal protective equipment was not adequate for their duties. Sixty-eight percent experienced burnout symptoms. Unavailability of personal protective equipment, negative concerns regarding the surgical career, and financial strains significantly affected the mental health of residents. CONCLUSIONS: The survey highlighted the negative impact of COVID-19 on neurosurgical practice and education. Being in a developing country, this negative effect was amplified due to financial reasons and weak infrastructure. Inadequate personal protective equipment increased the risk of infection and work-related stress among neurosurgery residents. We lacked telemedicine services in our country. Online education gained more visibility and awareness.